Зміни системи гемостазу у хворих на цукровий діабет 2-го типу з кардіоміопатією - Сергієнко, В. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
It was analysed the state of structurally — functional changes of cells membranes, basal membrane, pericapillarity space in 29 Type 2 diabetes mellitus patients with cardiomyopathy. It is established that diabetic cardiomyopathy is accompanied with activation of compensatory-adaptative processes, intensification of intracellular organelles activity, edema and hyperplasia of endotheliocytes that are accompanied by progressing of destructive endothelium changes. Simultaneously it is observed depressing of Na+, K+ -ATPase activity in the erythrocytes membranes, accumulation of lisosomes, triglicerides, lipofuscin in the cytoplasm, activation of lipid peroxidation. Progressing of diabetic cardiomyopathy is accompanied by compaction, but in some parts by loosening of basal membrane. Edema of interstitial spaces and accumulation of desintegration products of cells, triglicerides and glycoproteins are observed. This caused damaging of endothelial cells, rheological disorders and, insuring of vascular wall.